Visibilitas Website UIN Syarif Hidayatullah Jakarta dalam Pemeringkatan Webometrics - Parhan Hidayat; Muhammad Azwar (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2021)
This article attempts to describe the efforts to increase the visibility of the website of UIN Syarif Hidayatullah Jakarta in webometrics ranking. Webometrics is a means to measure the progress of a university through its website. This article aims to find the right work steps in an effort to increase website visibility and also the birth of practical steps to lift webometrics rankings that can be used as guidelines by website managers at UIN Syarif Hidayatullah Jakarta. This research uses a qualitative approach with a descriptive type. The main data was obtained using Focus Group Discussion (FGD) techniques by presenting parties related to webometrics ranking, having knowledge of SEO practices, and having experience in web management. The findings indicate that there have been efforts to increase the quantity and quality of content with the establishment of the publication and documentation division. There are still various obstacles to be faced, such as content management that does not meet SEO principles, several pages and subdomains that are not maintained, are damaged, and even lost, causing bad backlinks. It is necessary to build a website that uses the multisite method which is very effective and efficient in integrating various website needs at UIN Jakarta. The need for various efforts to overcome these obstacles, such as the need for effective communication between web development teams, the need for SEO-friendly content writing training, and the importance of SOPs in optimizing web performance and getting maximum webometrics ranking.